Advances in research on M1/M2 macrophage polarization in the pathogenesis and treatment of osteoarthritis - Zhijun Deng; Wenlong Yang; Bin Zhao; Zhijun Yang; Dian Li; Fengyun Yang (Heliyon)
Osteoarthritis (OA) is a chronic inflammatory joint disease associated with aging, trauma, obesity and other pathogenic factors. It is a leading cause of pain and disability worldwide. Macrophages, the most abundant immune cells in the synovium, display significant plasticity and heterogeneity, capable of polarizing into pro-inflammatory M1 or anti-inflammatory M2 types, thus playing a crucial role in the onset and progression of arthritis. Recent studies have increasingly focused on the important role of synovial macrophages in joint homeostasis and suggest that targeting macrophage polarization may emerge as a promising therapeutic strategy for osteoarthritis.